ANALISIS KONTRIBUSI DAN EFEKTIVITAS PENERIMAAN RETRIBUSI PELAYANAN PASAR TERHADAP PENDAPATAN ASLI DAERAH KOTA PALEMBANG - Sri Murniati; Dwi Kasasih (JURNAL KOMPETITIF, 2017)
The aim of this research is to determine and investigate the contribution of market retribution to original regional income at Palembang City and how the effectiveness of market retribution income. This research used a qualitative descriptive method. Based on the analysis result can be concluded that the contribution of market retribution against region income in 2011 amounted to 0.1579%, in 2012 the contribution amounted to 0.1791%, in 2013 the contribution amounted to 0.1841%, in 2014 the contribution amounted to 0.0813%, 2015 contribution amounting to 0.0304%. The effectiveness of the market retribution realization in 2011 amounted to 58.92% so it can be considered ineffective. The 2012 level of effectiveness by 100% so it can be considered effective. In 2013 the level of effectiveness of 100% so it can be considered effective. However, in 2014 the level of effectiveness by 3.95% so it can be considered ineffective, In 2015 the level of effectiveness of 11:18% so it can be considered ineffective. Key Words : Market Retribution, Regional Income, Contribution, Effectivenes